The first competitive ELISA for a sensitive and specific diagnosis of besnoitiosisis using a monoclonal antibody against Besnoitia besnoiti - Nascimento, Daniela Alcântara de Melo (2019)
Besnoitia (B.) besnoiti is a cyst-forming apicomplexan parasite responsible for bovine besnoitiosis, a re-emerging disease in Europe with both cutaneous and systemic manifestations. The significant morbidity, lack of treatment and production losses associated make specific, sensitive, rapid and economic diagnosis imperative. Thirteen monoclonal antibodies (mAbs) were previously produced against a membrane-enriched extracts of B. besnoiti tachyzoites (Apure-BbELISA Ag) and now characterized by Immunoblot assay and Indirect enzyme linked immunosorbent assay (iELISA). Hence, in order to meet the needs for a diagnostic method that would be accurate and easy to apply in the area of animal health, a study was undertaken to develop the first mAb-based competitive ELISA (Bb-cELISA1) at Friedrich-Loeffler-Institut (FLI) in Germany. A total of 948 cattle sera were used to evaluate the Bb-cELISA1. The results were compared with previous iELISA results and revealed 99 per cent sensibility and 99.7 per cent specificity; Resumo: O primeiro ELISA de competição para um diagnóstico sensível e específico de besnoitiose utilizando um anticorpo monoclonal contra Besnoitia besnoiti Besnoitia (B.) besnoiti é um parasita apicomplexa formador de quistos, responsável pela besnoitiose bovina, uma doença re-emergente na Europa com manifestações cutâneas e sistémicas. A morbilidade, inexistência de tratamento e perdas produtivas associadas, tornam imperativo um diagnóstico específico, sensível, rápido e económico. Treze anticorpos monoclonais (mAbs) anteriormente produzidos face a um extrato de membrana enriquecida de taquizoítos de B. besnoiti (Apure-BbELISA Ag) foram agora caracterizados através de Immunoblot e Indirect enzyme linked immunosorbent assay (iELISA). Consequentemente, com o objetivo de encontrar um método diagnóstico que seja exato e fácil de aplicar na área da saúde animal, o trabalho foi realizado para desenvolver o primeiro mAb-based ELISA competitivo (Bb-cELISA1) no Friedrich-Loeffler-Institut (FLI) na Alemanha. Foram utilizados 948 soros de bovino para avaliar o Bb-cELISA1. Os resultados foram comparados com resultados anteriores de iELISA e reveladas sensibilidade de 99,1 por cento e especificidade de 99,7 por cento.